Trends in primary brain tumors: A 5-year retrospective histologically confirmed study in Tabriz, Iran, 2011–2016 - Salehpour, Firooz; Mirzaei, Farhad; Meshkini, Ali; Parsay, Sina; Salehi, Sana; Asl, Mohammad (Asian Journal of Neurosurgery, 2019)
Introduction: Tumors are the second-most common cause of death after cardiovascular diseases. Due to the high prevalence and mortality rate, brain tumors are of great importance and makeup about 5% of all tumors. Different types of brain tumors have their special pattern based on age, sex, complaints on admission, radiological signs and sometimes, their family history and seem these patterns are changing according to the geographic region over time. In this study, we evaluate the incidence of brain tumors in the northwest of Iran. Materials and Methods: All patients with brain tumor diagnosis that were hospitalized between April 2011 and March 2016 evaluated. Exclusion criteria were considered as secondary tumors of the central nervous system (CNS) (metastases) and duplicate records for the recurrent disease of the same patient. Data collected from their documents and analyzed with SPSS version 16. Results: In the present study, male to female (M: F) ratio is 1:1. 92.5% of tumors are primary in which meningiomas (22%) and glioblastoma multiforme (GBM) (19.6%) are the most common types. The rarest tumor types are neurocytoma (0.3%) and chondroid chordoma (0.3%). GBM is the most common tumor in the male population and meningiomas are most common in females. Medulloblastoma and meningioma with a median age of 11 and 58 years, respectively, were known as the most common primary CNS malignancy of the youngest and oldest age of study group. Conclusion: The obtained data from this study revealed that age and sex are associated with the tumor types, which is consistent with the previous results. Brain tumors involvement pattern is changing in male patients somehow there is a tendency of involving more aggressive and malignant tumor types in male individuals could be seen.
Keywords: Brain tumor; epidemiology; primary central nervous system tumors; prevalence; tumor types